Biochemical diversity in Allium species: key metabolite profiles for breeding and bioprospecting - Benke, Ashwini Prashant; Mokat, Digambar; Mahajan, Vijay (Frontiers in Plant Science, 2025)
The genus Allium encompasses a diverse range of species, including cultivated, wild, and underutilized varieties, each exhibiting significant biochemical diversity. This study aims to comprehensively analyze the phytochemical composition and biochemical variability in 19 Allium germplasm representing 16 species. The research focuses on key bioactive compounds such as flavonoids, phenolics, sulfur-containing compounds, and sugars to provide valuable insights for breeding programs, functional food development, and pharmaceutical applications. Biochemical profiling was conducted using standard assays (qualitative and quantitative) to determine antioxidant activity, thiosulfinate content, pyruvic acid levels, and sugar content. To analyze the data, hierarchical clustering analysis was performed to group the species, and Principal Component Analysis (PCA) was used to explain the total biochemical variance and differentiate the species based on their metabolic composition. The analysis revealed substantial variations across species. The average thiosulfinates content ranged from 5.33 to 26.12 µmol/g FW, total flavonoid content from 10.42 to 48.42 mg/100 g FW, and total phenolic content from 7.76 to 21.00 mg/100 g FW. The highest antioxidant activity (DPPH assay) was 6.05 µmol/g FW, while total sugar levels ranged from 0.51 to 8.79 g/100 g FW. The hierarchical clustering analysis grouped the Allium species into two major clusters: Cluster 1 (10 domesticated accessions) and Cluster 2 (9 wild and underutilized accessions). The clustering was driven primarily by thiosulfinate content, pyruvic acid levels, flavonoid content, and antioxidant activity, with wild species showing significantly higher concentrations of bioactive metabolites. The PCA explained 66.1% of the total biochemical variance, with PC1 contributing 38.5% and PC2 contributing 27.6%. Strong positive correlations were observed between total flavonoid content and antioxidant activity (r = 0.91, p < 0.001), total phenolic content and allicin (r = 0.87, p < 0.001), and total pyruvic acid and enzymatically produced pyruvic acid (r = 0.93, p < 0.001). This study underscores the significance of biochemical characterization in understanding the nutritional and medicinal potential of Allium species. The findings indicate a potential co-regulation of these biochemical pathways, as suggested by the strong positive correlations between key compounds. The results offer valuable insights for selecting superior Allium genotypes with enhanced bioactive properties, which is crucial for future interspecific Allium breeding programs and the development of new functional foods and pharmaceuticals.